PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP LOYALITAS KARYAWAN PDAM SITUBONDO DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Riyanti, Lisa; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
PDAM Tirta Baluran Situbondo is a company dedicated to providing clean water access to the Situbondo community. The village's water needs are met through the efforts of PDAM Tirta Baluran Situbondo, which ensures the availability of clean water. Given the essential role water plays in sustaining human life, its significance is undeniable. Historical records from the water tower in Situbondo's city square indicate that water development initiatives were initiated by the Dutch East Indies government in 1936, specifically in the Situbondo Regency. Following Indonesia's Independence, the management of water development was transferred to the government in Panarukan. The research methodology includes data analysis and hypothesis testing using the Structural Equation Model - Partial Least Square (PLS-SEM). The outcomes of hypothesis testing through the application of Smart PLS 3.0 reveal that motivation significantly and positively affects job satisfaction. Compensation also has a significant positive influence on job satisfaction. Moreover, motivation considerably contributes to loyalty, while compensation shows a noteworthy negative impact on loyalty. Additionally, job satisfaction plays a significant role in fostering loyalty. Furthermore, the positive impact of motivation on loyalty, mediated by job satisfaction, is noteworthy. Similarly, compensation's positive effect on loyalty, mediated by job satisfaction, is notable.